(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the stages of the study and development of the life and statehood of Amir Temur in Turkish historiography. In this study, the reasons were found that led to the study of Sahibkiran by Ottoman and modern Turkish temurologists.